Let’s Learn Mandarin! : A Chinese Language Vocabulary Learning Mobile Application For 7 Years Old Children - Tan, Yan You; Che Dalim, Che Samihah (Applied Information Technology And Computer Science, 2022)
The number of children enrolling in Chinese schools to learn the language increases year by year. Therefore, a Chinese vocabulary learning mobile application, Let’s Learn Mandarin! will be developed by targeting 7-year-olds to learn Chinese language vocabulary during leisure time. This application aims to address the shortcomings of some equivalent applications, such as the failure to implement attractive and interactive multimedia elements, boring learning content, and confusing navigational structure. This project aims to develop the proposed learning mobile application using 2D trivia gamification approach on Android using Unity. After completed the development of the application, beta testing is carried out in the form of user acceptance test among Year 1 students in S.J.K. (C) Saleng. The results from the user acceptance test showed that the application received positive feedbacks from its target users. Therefore, it is said that the objectives of this project are achieved. Besides, the advantages, limitations, and future works of Let’s Learn Mandarin! had also being identified in the end of the project.